JBAH 2021
DOI: 10.7176/jbah/11-3-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Classification of Soils of Askate Sub-watershed, South Wollo Zone, Northeastern Ethiopia

Abstract: Information on soil is an essential in sustainable utilization of soil resources and sound land use planning. Therefore, this study was conducted with the objective of characterization and classification of soil on Askate sub-watershed, northeastern Ethiopia. Four representative soil pedons were opened along topographic position and described on each identified genetic horizons basis on the field for their morphological characteristics following the soil field description guidelines. The morphological properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The same trend of TN and OC may indicate that organic matter is also a major source of TN. In line with current nding several studies indicated a strong positive relation between TN and OC 23,34,35 . The C/N demonstrated inconsistency with depth in all pedons and slope position of the studied area.…”
Section: Soil Organic Carbon Total Nitrogen and C: N Ratiosupporting
confidence: 89%
See 1 more Smart Citation
“…The same trend of TN and OC may indicate that organic matter is also a major source of TN. In line with current nding several studies indicated a strong positive relation between TN and OC 23,34,35 . The C/N demonstrated inconsistency with depth in all pedons and slope position of the studied area.…”
Section: Soil Organic Carbon Total Nitrogen and C: N Ratiosupporting
confidence: 89%
“…Several researchers reported similar trends to the current study. Accordingly, 24,35,40 reported higher levels of extractable micronutrients in surface horizons than in subsurface horizons because of the high OM and low pH on the surface soil.…”
Section: Exchangeable Bases and Ca/mg Ratiomentioning
confidence: 99%